IMPLEMENTASI MANAJEMEN KEDISIPLINAN: UPAYA MENINGKATKAN KONSISTENSI IBADAH SANTRI DI PESANTREN - Ahmad Azaim Multazami; Eka Diana (Jurnal Manajemen Pendidikan, 2025)
This study aims to describe the strategy for managing students' religious discipline at the Nurul Jadid Islamic Boarding School in the Sunan Muria area. The main focus of the study is how the Islamic boarding school fosters and maintains consistent religious practices amidst the challenges of the digital era. A qualitative case study approach was used. Data were obtained through observation, interviews, and documentation. The results indicate that religious discipline management is implemented through a combination of structural and cultural approaches. A flagship program, such as resettlement, is the primary strategy for addressing students experiencing a decline in religious discipline. Supervision is conducted in a multi-layered, community-based manner, coupled with habituation and role modeling. Local Islamic boarding school wisdom, such as the barzanji (prayer) and night deliberations (musyawarah malam), is also utilized as a means of internalizing disciplinary values. This study concludes that the management of religious discipline not only fosters formal compliance but also fosters a deep and sustainable religious awareness.